Clicks and Identity: Analyzing How Online Advertisement Interaction Affects Buying Behavior Among Tasya Farasya's Followers - Raudhatul Rizka; Napitupulu, Priskilla E.E. (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
A global trend where influencers play an important role in digital marketing strategies. Tasya Farasya as one of Indonesia's leading beauty influencers offers a unique context to investigate this dynamic. There are still few studies that specifically explore how psychological factors such as trendiness, relaxation, boredom, and information seeking influence followers' buying behavior in clicking on online advertisements and social influencers with influencerproduced content. This study aims to analyze how these factors influence followers' buying behavior tendencies through clicking online advertisements and social influencers with content produced by Tasya Farasya's Instagram account. Using quantitative methods, data was collected through questionnaires distributed to 120 followers of Tasya Farasya's Instagram account, in Indonesia. This research includes into the category of causal research. The sampling technique used is non-probability sampling technique. Using Smart PLS 4 to process data. Of the eight hypotheses, there are two rejected hypotheses, namely trendiness has no significant effect on online advertisement clicking and social identification has no significant effect on buying behavior, others have a significant effect. Tasya Farasya's influence increases ad visibility, and encourages her followers' buying behavior.